ASSESSMENT OF THE IMPACT OF GURARA DAM ON LAND USE/LAND COVER IN THE SURROUNDING COMMUNITIES OF KACHIA LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - GIMBA, B.E; KWALLAH, S.M; YAKUBU, M.D (FUDMA Journal of Earth and Environmental Sciences, 2024)
The study assessed the impact of Gurara Dam on land use/land cover changes (LULCC) in the Kachia Local Government Area of Kaduna State. The study made use of geospatial techniques to assess the impact of the dam on land use/land cover changes within the period of study. Landsat data from 2001, 2012 and 2022 were acquired and processed to produce the land use/land cover maps of the area. The identified land use/land cover in the area were Built-up areas, Water bodies, Vegetation, bare land, and Rock outcrops. The Annual rate in land use/landcover changes was analyzed and the result revealed that, during the period 2001-2012, and 2012-2022 water bodies increased at an annual rate of 242% and 97% but reduced at an annual rate of 0.9%between 2012 and 2022. The analysis revealed that all the land use/land cover types identified in the study area recorded a net gain except vegetation. Water bodies gained about 5480 ha from 2001 to 2022. The study concluded that the construction of the Dam has altered the land use land cover dynamics of the area and there is also evidence of deforestation in the study area. The study recommends the control of land use in the basin and uses it as a guide to help in prioritizing the management of the basin and the dam among others.